2011
DOI: 10.1088/0029-5515/51/8/083049
|View full text |Cite
|
Sign up to set email alerts
|

Achievement of 500 keV negative ion beam acceleration on JT-60U negative-ion-based neutral beam injector

Abstract: Hydrogen negative ion beams of 507 keV, 1 A and 486 keV, 2.8 A have been successfully produced in the JT-60U negative ion source with a three-stage accelerator by overcoming a poor voltage holding of the accelerator with large-size grids of ∼2 m2. This is the first result of H− beam acceleration up to 500 keV at a high current of over 1 A. In order to improve the voltage holding capability, the breakdown voltages of the large-size grids and small-size electrodes with uniform and locally strong electric fields … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…High-energy neutral beam injection (NBI) plays an important role for a magnetically confined fusion device for heating and current drive [1,2,3,4,5,6]. We have achieved 16 MW beam injection using 3 beam lines with 6 large scaled hydrogen negative ion (H − ) sources in the Large Helical Device (LHD) [3].…”
Section: Introductionmentioning
confidence: 99%
“…High-energy neutral beam injection (NBI) plays an important role for a magnetically confined fusion device for heating and current drive [1,2,3,4,5,6]. We have achieved 16 MW beam injection using 3 beam lines with 6 large scaled hydrogen negative ion (H − ) sources in the Large Helical Device (LHD) [3].…”
Section: Introductionmentioning
confidence: 99%
“…As this field marginally penetrates in the plasma source upstream of the PG, it also enhances the extraction of negative ions and reduces the co-extracted electrons. As in most of the existing experiments, the Suppression Field is generated by arrays of permanent magnets embedded in the EG and has two opposite peaks of about 50 -60 mT along each beamlet, in order to reduce the resulting deflection of the ions [7]. Nevertheless, numerical simulations and experiments on the MeV Test Facility at JAEA Naka (Japan) have shown that this field can degrade the final beam optics by introducing a zig-zag deflection of some mrad on the ion beamlets.…”
Section: Basic Design Requirements For Spider and Mitica Magnetic Fieldmentioning
confidence: 99%
“…For multi-stage accelerators operating at higher acceleration voltage, the CESM magnets on the EG are not sufficient to prevent a large number of stripped electrons from being accelerated and reaching the accelerator exit. To this purpose an additional transverse magnetic field produced by a current flowing in the PG (long-range electron Suppression Field) has been successfully used for reducing the average number and energy of the electrons at the accelerator exit in the JT-60U injector at JAEA (Naka, Japan) [7].…”
Section: Magnetic Field In the Accelerator: Local And Long-range Compmentioning
confidence: 99%
“…Large size and high current NBI systems used arc discharge type H -sources have been operated successfully in the Large Helical Device (LHD) [1] and JT-60U [2] in Japan. A larger H -source used RF discharge was developed at Max-Plank Institute fur Plasma Physics in Garching [3].…”
Section: Introductionmentioning
confidence: 99%